The Effect of SAQ Training (Speed, Agility, and Quickness) and Balance on Yeop Chagi Taekwondo Kicking Skills - Sumarna, Laras Fitriana Novianty; Siregar, Nofi Marlina; Lubis, Johansyah (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
The background of this research is the low skill of 9 year old athletes in performing the yeop chagi taekwondo kick movement. This study aims to analyze the effect of SAQ and balance training on Yeop Chagi Taekwondo kicking skills. The research method used was an experimental method with a treatment design by level 2 x 2. The research subjects were 32 Fazz Taekwondo Team Bandung athletes, divided into two groups, each group consisting of 16 people. The results of the research are as follows: 1) the yeop chagi taekwondo kicking skills of Fazz Taekwondo Team athletes using ladder drills for poomsae training (mean = 99.50 and s = 2.90) are better than the yeop chagi taekwondo kicking skills using ladder drills training (mean = 99.25 and s = 4.25). 2) Fcount of interaction (FAB) = 8.796, with p-value 0.006 < 00.5, so H0 is rejected and H1 is accepted. 3) the value of Qcount (Qh) = 6.19 is greater than Qtable = 4.05 or Qcount > Qtable at the significance level α = 0.05. This means that there is a difference between ladder drills for poomsae training and ladder drills training for yeop chagi taekwondo kicking skills in athletes who have high balance. 4) Qcount (Qh) = 5.67 is greater than Qtable = 4.05 or Qcount < Qtable. This means that there is a difference between ladder drills for poomsae training and ladder drills training for yeop chagi taekwondo kicking skills in athletes who have high balance. Thus, it can be concluded that overall there is an influence of SAQ and balance training on Yeop Chagi Taekwondo Kick skills.